Pengaruh Opportunistic Behaviour dan Love of Money Perangkat Desa Terhadap Pengelolaan Keuangan Desa dan Dampaknya Terhadap Kesejahteraan Masyarakat - Sholehah, Nur Lazimatul Hilma; Ishak, Parmin (Universitas Gorontalo, 2022)
The study was conducted to learn of the immediate and indirect relationships of qualistic practices and the love of money towards the management of village finances and the impact on the public welfare of the wonosari district. The study USES a quantitative method. The methods of data collection used in the study are carried out through field observation, disseminating questionnaires, interviews, documentation and literature studies. As for the population in this research is an entire kit of villages in the boalemo district with a sampling withdrawal using sampling clusters. The data analysis technique used in the research is a path analysis technique with the help of version 24 of SPSS software. The results of the study indicate that (1) qualistic traits negatively and significantly affect the village's financial management, (2) love of money makes no significant difference to the village's financial management, (3) provocistic practices indirectly affect both the positive and significant well-being of the village through village financial management, (4) love of money indirectly affects the welfare of the village by managing the village's finances, (5) village finance management has a positive and significant impact on village fund management.